DNA Biomaterial Based Fiber Optic Sensor: Characterization and Application for Monitoring in situ Mercury Pollution. Issue 11 (26th July 2016) - Polley, Nabarun; Sarkar, Probir Kumar; Chakrabarti, Subhananda; Lemmens, Peter; Pal, Samir Kumar
Abstract: In recent years considerable efforts have been devoted to utilize DNA based biomaterials for efficient sensor design. The polymeric molecule has high aqueous solubility, thus design of any water based sensor with DNA without rigorous chemical treatment (modification for covalent bonding) is challenging. In the present work we have developed a novel silver‐nanoparticle (Ag‐NPs) impregnated genomic DNA‐lipid (CTAB) complex, which is completely insoluble in water and forms excellent thin film on optical fiber tips. The intact structural as well as functional integrity of the genomic DNA in the thin film is found to be a key factor for its specific affinity to mercury ions in aqueous environments. We have demonstrated that a dip‐coated optical fiber tip can work as a fluorescence sensor in addition to a surface plasmon resonance (SPR) type absorption sensor due to nano surface energy transfer (NSET) between the DNA minor‐groove binding dye 4′, 6‐diamidino‐2‐phenylindole (DAPI) and Ag‐NPs. Nanomolar, specific detection of mercury ions with few seconds reaction time is found in this versatile and economic way revealing clearly the advantageous aspects of our work. Abstract : Silver‐nanoparticle (Ag‐NPs) impregnated genomic DNA‐lipid (CTAB) complex is insoluble in water and can form excellent thin film. A dip‐coated optical fiber tip can work as a fluorescence sensor in addition to a surface plasmon resonance (SPR) type absorption sensor of mercury ions. The nano surface energy transfer (NSET) between the DNA minor‐groove binding dye 4′, 6‐diamidino‐2‐phenylindole (DAPI) and Ag‐NPs is pertrubed upon interaction with Hg 2+ due to amalgamation between Ag‐NPs and Hg 2+ (De‐NSET), hence emission of DAPI is restored.